A detailed techno-economic analysis of heat integration in high temperature electrolysis for efficient hydrogen production. (5th January 2015) - Buttler, Alexander; Koltun, Roman; Wolf, Romano; Spliethoff, Hartmut
Abstract The effect of high temperature heat utilization in solid oxide electrolysis on efficiency and hydrogen specific cell area is investigated based on a detailed 1-D electrochemical model validated with literature data. A first feasibility analysis indicates that the mean heat transfer required to maintain isothermal conditions as a function of heat integration shows a maximum with 1426 W/m2 at a heat utilization of 0.34 kWh/Nm3 H2, which seems to be technically achievable. Based on the assumption of future specific cell area costs of 1500 €/m2 high temperature heat integration of 0.24 kWh/Nm3 is economically reasonable resulting in a reduction of the specific electric energy consumption by 7.8% (2.82 kWh/Nm3) compared to thermo-neutral operation. An extensive sensitivity analysis indicates increased electricity prices and higher lifetime of the solid oxide electrolysis cell (SOEC) stack as major parameters favoring direct heat utilization, while decreasing utilization for power-to-gas storage applications is counteracting.